The Regulatory Role of GBF1 on Osteoclast Activation Through EIF2a Mediated ER Stress and Novel Marker FAM129A Induction - Wen, Cailing; Zhou, Yuheng; Xu, Yanting; Tan, Huijing; Pang, Caixia; Liu, Haiqian; Liu, Kaifei; Wei, Linlin; Luo, Hui; Qin, Tian; He, Chonghua; Liu, Cuiling; et al. (Frontiers in Cell and Developmental Biology, 2021)
Bone-resorbing activities of osteoclasts (OCs) are highly dependent on actin cytoskeleton remodeling, plasma membrane reorganization, and vesicle trafficking pathways, which are partially regulated by ARF-GTPases. In the present study, the functional roles of Golgi brefeldin A resistance factor 1 (GBF1) are proposed. GBF1 is responsible for the activation of the ARFs family and vesicular transport at the endoplasmic reticulum–Golgi interface in different stages of OCs differentiation. In the early stage, GBF1 deficiency impaired OCs differentiation and was accompanied with OCs swelling and reduced formation of mature OCs, indicating that GBF1 participates in osteoclastogenesis. Using siRNA and the specific inhibitor GCA for GBF1 knockdown upregulated endoplasmic reticulum stress-associated signaling molecules, including BiP, p-PERK, p-EIF2α, and FAM129A, and promoted autophagic Beclin1, Atg7, p62, and LC3 axis, leading to apoptosis of OCs. The present data suggest that, by blocking COPI-mediated vesicular trafficking, GBF1 inhibition caused intense stress to the endoplasmic reticulum and excessive autophagy, eventually resulting in the apoptosis of mature OCs and impaired bone resorption function.